Evaluation of yield of small-fruited bitter gourd (Momordica charantia) under saline soil (Current Horticulture, 2024)
Small-fruited bitter gourd [Momordica charantia L. var. muricata (Willd.) Chakrav.] grows well in tropical and subtropical climates. This species needs to be conserved (Bano and Sharma, 2017). Momordica charantia var. charantia is crossable with Momordica  charantia var. charantia (Vijayakumar et al.,2019). It is an herbaceous vine and does not require pandal (support). It grows up to a length of 1.5 m on the ground. The vines have deeply lobed leaves, yellow flowers and very small fruits without grooves. It is cultivated in Tamil Nadu for its excellent taste and texture after cooking. It fetches price of 25-40 % more than large type bitter gourd. It performs well in soil with a good drainage facility. Keeping in view, an experiment was conducted to find out its cultivation under saline soil.